Remote Management of Prosthodontic Emergencies in the Geriatric Population During the Pandemic Outbreak of COVID-19 - Aldhuwayhi, Sami; Shaikh, Saquib Ahmed; Thakare, Amar Ashok; Mustafa, Mohammed Ziauddeen; Mallineni, Sreekanth Kumar (Frontiers in Medicine, 2021)
The global pandemic outbreak of coronavirus disease 2019 (COVID-19) has put the world in a panic situation. It has been evident that the geriatric population is more susceptible to acquire this infection. Thus, due to this ongoing crisis, geriatric individuals cannot visit a dental operatory, and there is the possibility of their dental needs and emergencies to remain unattended. Partial or complete edentulism is very prevalent among the geriatric population, and prosthodontic management of these patients is essential for their well-being. However, the prosthesis can lead to various emergencies of the oral and its supporting structures. There are currently no available recommendations to address these prosthodontic emergencies in geriatric individuals during this pandemic period. Hence, the aims of this minireview were to discuss the common prosthodontic emergencies in the geriatric population and provide recommendations to manage these issues during the COVID-19 pandemic outbreak.